Association between Oxidative Stress and Outcome in Different Subtypes of Acute Ischemic Stroke. (8th May 2014) - Tsai, Nai-Wen; Chang, Ya-Ting; Huang, Chi-Ren; Lin, Yu-Jun; Lin, Wei-Che; Cheng, Ben-Chung; Su, Chih-Min; Chiang, Yi-Fang; Chen, Shu-Fang; Huang, Chih-Cheng; Chang, Wen-Neng; Lu, Cheng-Hsien
Abstract : Objectives . This study investigated serum thiobarbituric acid-reactive substances (TBARS) and free thiol levels in different subtypes of acute ischemic stroke (AIS) and evaluated their association with clinical outcomes. Methods . This prospective study evaluated 100 AIS patients, including 75 with small-vessel and 25 with large-vessel diseases. Serum oxidative stress (TBARS) and antioxidant (thiol) were determined within 48 hours and days 7 and 30 after stroke. For comparison, 80 age- and sex-matched participants were evaluated as controls. Results . Serum TBARS was significantly higher and free thiol was lower in stroke patients than in the controls on days 1 and 7 after AIS. The level of free thiol was significantly lower in the large-vessel disease than in the small-vessel disease on day 7 after stroke. Using the stepwise logistic regression model for potential variables, only stroke subtype, NIHSS score, and serum TBARS level were independently associated with three-month outcome. Higher TBARS and lower thiol levels in the acute phase of stroke were associated with poor outcome. Conclusions . Patients with large-vessel disease have higher oxidative stress but lower antioxidant defense compared to those with small-vessel disease after AIS. Serum TBARS level at the acute phase of stroke is a potential predictor for three-month outcome.